ANALISIS FAKTOR YANG MEMPENGARUHI PERTUMBUHAN KULTUR SEL CHO (Chinase Hamster Ovarium) PADA PEMBUATAN OBAT TRASTUZUMAB DI PT. BIO FARMA - Silitonga, Maringan; Chandra, Devina; Fitri, Raissa; Nanda, Farahlina (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
This study examines what factors can affect the growth of CHO cell cultures which are often used in biological and medical research and commercially in the production of therapeutic proteins. The purpose of this study was to determine whether CHO cells were able to grow and reproduce with the process flow and manufacturing method of drug preparations in accordance with the requirements of the applicable legislation. The workings of this research are divided into two stages, namely the microbiological stage and the biotechnology stage. The microbiological stage begins with making a working culture, then purification is carried out for culture rejuvenation, harvesting, cell culture breakdown, and purification of target cells. At the biotechnology stage, protein measurements were carried out, Optical Density 600 observations, polyacrylamide gel SDS electrophoresis, and gel electrophoresis staining.